2015
DOI: 10.1002/app.42046
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of sulfonated fluorinated block copolymer membranes with different esterified initiators for DMFC applications

Abstract: This investigation studied the synthesis of ionic membranes composed of a sulfonated poly(styrene‐isobutylene‐styrene) with novel fluoroblock copolymers. These fluoroblock copolymers were synthesized using three different initiators by Atom Transfer Radical Polymerization (ATRP); two fluoroinitiators were obtained from the esterification of 2‐(perfluoroalkyl) ethanol or octafluoro 4‐4′‐biphenol. The third initiator evaluated was 1‐bromoethyl benzene. The resulting block copolymers were characterized using seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 51 publications
0
11
0
2
Order By: Relevance
“…It should be noted that the relative increase in methanol permeability at higher fluoropolymer composition (70%) is not as large as the increase in proton conductivity (418%). Although the transport mechanism for protons and methanol is similar, studies suggest that the methanol permeability is more sensitive to free volume and to changes in chemical composition, while changes in morphology could lead to more significant differences in the transport mechanism of both protons and methanol .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It should be noted that the relative increase in methanol permeability at higher fluoropolymer composition (70%) is not as large as the increase in proton conductivity (418%). Although the transport mechanism for protons and methanol is similar, studies suggest that the methanol permeability is more sensitive to free volume and to changes in chemical composition, while changes in morphology could lead to more significant differences in the transport mechanism of both protons and methanol .…”
Section: Resultsmentioning
confidence: 99%
“…However, the maximum value of methanol permeability was reached at a higher correlation length. Studies suggested that variations between the proton conductivity and methanol permeability in SIBS SO 3 H are related to competing effects that depend on the free volume . Figure shows the relationship between the proton conductivity, water content, IEC, correlation length for hydrated membrane, and polymer percent of PHFBMA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have suggested that this behavior also occurs due to a reduction in P MeOH attributed to reduced dimensions of ionic clusters and interfacial interactions between fillers and the functionalized polymer [12,29]. The methanol permeability of a PEM is usually influenced by its morphology [61]. However, no correlation is observed between P MeOH and the morphology of the PEMs.…”
Section: Transport Propertiesmentioning
confidence: 99%